PENGARUH MEDIA COUNTING BOX TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN MATEMATIKA - Mudtalifah; Mansur; Oman Farhurohman (STKIP Subang, 2024)
The aim of this research is to determine whether or not there is an influence of using Counting Box media on students' critical thinking skills in mathematics learning about fractions. The methodology used in this research isPre-Experiment. The research design used was One-Group Pretest-Posttest. The subjects of this research were students in class III, even semester, at SD Negeri Tanjung Ilir. Data collection techniques in research are using oral tests, interviews and documentation. The results are shown from the average pretest score of 30.32. After being treated with counting box media, the average post-test score increased to 77.78. This shows that the Counting Box media has an effect on improving students' critical thinking abilities and can be used as a recommended learning media for mathematics learning.